Tooth wear and erosive tooth wear among 16-year-old Malaysian adolescents - Ab Halim, Noorhazayti; Esa, Rashidah; Chew, Hooi Pin (Malaysian Public Health Physicians’ Association, 2013)
Introduction: General tooth wear (GTW) (indiscriminate of aetiology) and more specifically erosive wear (ETW) are relatively new emerging public health problems globally. Study about their prevalence has not been sufficiently explored in Malaysia. This study aimed to determine the prevalence and severity of GTW and ETW among 16-year-old adolescents in Kuantan, Malaysia.